A new species of narrow-banded Cyrtodactylus (Gekkonidae) from northern New Guinea - Oliver, Paul M.; Boothroyd, Nicholas; Tjaturadi, Burhan; Riyanto, Awal; Iskandar, Djoko T.; Richards, Stephen J. (Zootaxa, 2024)
We describe a new species of Cyrtodactylus from the northern lowlands and foothills of mainland New Guinea. Cyrtodactylus mamberamo sp. nov. is distinguished from all other Melanesian Cyrtodactylus except C. aaroni and C. mimikanus by the combination of moderate size (max SVL <100 mm), widened subcaudals, dorsal pattern of numerous narrow light bands with dark-brown anterior borders, and a tripartite pore arrangement in males. It differs from these two most-similar species in details of colour pattern, scalation and the number of precloacal pores. Cyrtodactylus mamberamo sp. nov. occurs at elevations between 0–870 m above sea level (a.s.l.) across a wide area spanning the Mamberamo Basin and nearby regions. It co-occurs with at most one or two other congeners. Low Cyrtodactylus alpha diversity across Melanesia emphasises beta turnover as the key factor underpinning species richness in this genus. The new species brings the total number of recognised Melanesian Cyrtodactylus to 35, with the real total certain to be over 40 species.